Cursebound : a novel - El-Arifi, Saara (El-Arifi, Saara. Faebound trilogy, 2025)
"Yeeran and Lettle are no longer prisoners to the fae court, but now they're bound by shackles of their hearts, in this sequel to Faebound from the national bestselling author. United by war. Betrayed by destiny. Cursed by love"--